Well-being in post-primary schools in Ireland: the assessment and contribution of character strengths. Issue 2 (3rd April 2019) - Burke, Jolanta; Minton, Stephen James
Abstract : Enhancing the well-being of primary and post-primary students is one of the priorities of the Department of Education and Skills in Ireland. Whilst interventions are being implemented across the board, little is known about the current levels of adolescents' well-being. Drawing from research on positive education, in the current study well-being was assessed amongst 2822 adolescents, aged 12–19 in Ireland, using the PERMA profiler [Butler, J., and M. L. Kern. (2016). "The PERMA-Profiler: A Brief Multidimensional Measure of Flourishing." International Journal of Wellbeing 6 (3): 1–48. doi:10.5502/ijw.v6i3.526 ] and "VIA-Youth Survey" [VIA Character (2014).http://www.viacharacter.org/www/Research-Old2/Psychometric-Data-VIA-Youth-Survey ]. Mann–Whitney U -test and multiple regression analyses were conducted in the examination of age and sex differences in students' well-being scores, and the prediction of the contribution of character-strength-development to well-being. The results showed that students' well-being decreased steadily from the first year, through to the middle and senior years of post-primary school. Furthermore, in comparison to males, females reported lower levels of well-being across the board, and higher levels of negative emotions and loneliness. Finally, the underuse of character strengths predicted lower levels of well-being in Irish schools. Implications for practice include the importance of customising well-being programmes across different schools and age groups, as well as the potential for the incorporation of psychological tests to evaluate the effectiveness of such interventions.